2022
DOI: 10.3389/fphar.2022.988512
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of helper T cell type 1, helper T cell type 2 and associated cytokines in patients with systemic lupus erythematosus: A meta-analysis

Abstract: Objective: Th1 and Th2 cells and their associated cytokines function in the pathogenesis of systemic lupus erythematosus (SLE), but their exact roles are uncertain. We performed a meta-analysis to examine the relationship of these cells and cytokines with SLE.Methods: Multiple databases were searched to identify publications that reported the percentages of Th1 and Th2 cells and their associated cytokines in SLE patients and healthy controls (HCs). Meta-analysis was performed using Stata MP version 16.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…The pro-inflammatory cytokines, which infer IL-6 as a mediator of disease initiation, increase the susceptivity of the vascular pathology in MRL-Fas lpr mouse model [ 34 ]. A meta-analysis suggested that the levels of IL-6 and TNF- α in SLE patients were higher than in healthy controls [ 35 ]. Compared to B6.lpr, the proteins of IL-6 and TNF- α in macrophage culture supernatant in B6.∆sNASP.lpr mice were significantly higher, and the level of the mRNA was also increased by LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pro-inflammatory cytokines, which infer IL-6 as a mediator of disease initiation, increase the susceptivity of the vascular pathology in MRL-Fas lpr mouse model [ 34 ]. A meta-analysis suggested that the levels of IL-6 and TNF- α in SLE patients were higher than in healthy controls [ 35 ]. Compared to B6.lpr, the proteins of IL-6 and TNF- α in macrophage culture supernatant in B6.∆sNASP.lpr mice were significantly higher, and the level of the mRNA was also increased by LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The proinflammatory cytokines, which infer IL-6 as a mediator of disease initiation, increase the susceptivity of the vascular pathology in MRL-Fas lpr mouse model [34]. A meta-analysis suggested that the levels of IL-6 and TNF-α in SLE patients were higher than in healthy controls [35]. Compared to B6.…”
Section: Discussionmentioning
confidence: 99%
“…Activated naïve CD4+ T cells proliferate and differentiate into effector T helper cells. Overactivation of T-cells results in the amplification of inflammation via secretion of pro-inflammatory cytokines, hyperactivation of B-cells leading to the generation of autoantibodies and further production of immune complexes and immunoglobulins, and maintenance of SLE via the retention of autoreactive memory T cells (Suárez-Fueyo et al, 2016;Xiang et al, 2022) (figure 2). Despite decades of research, the pathogenesis of SLE is yet to be understood entirely.…”
Section: The Pathogenesis Of Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Type 2-related immune response is common in more than 50% of SLE patients [2]. Abnormal Th2-associated immunity is more frequent in elderly and male SLE patients [3], while the detailed molecular mechanism for this discrepancy has not been verified. Identifying new strategies targeting checkpoint molecules involved in Th2related immunity is urgent for the targeted treatment of SLE.…”
mentioning
confidence: 99%